Obesity health and economic consequences of an impending global challenge - Meera Shekar, Barry Popkin (World Bank Group, 2019)
"Obesity is a global ticking time-bomb with huge potential negative economic and health impacts, especially for the poor. Countries and global partners need to act urgently to address this ensuing epidemic with emphasis highlighting interventions that require corrective public action rather than one of individual responsibility"--